Modeling of Waste Heat Recovery System and Effects at Different Engine Operating Conditions. (10th July 2014) - Tu, Ming; Li, Gangyan; Hu, Jian
Abstract : The model of waste heat recovery (WHR) system is considered by using the thermodynamics cycle, organic Rankine cycle (ORC), to reutilize the waste heat from engine exhaust gas. The model was validated and then applied to different operating conditions. From the results, it could be seen that the working fluid mass flow rate, engine speed, and system pressure would determine the output power and thermal efficiency; the working fluid mass flow rate need not be fixed at a certain point, but a wider range mass flow rate could be chosen with increasing the engine speed; the system pressure could improve the system thermal efficiency resulting in improving the engine thermal efficiency. Besides that, the model also applied to the test cycles which the engine is not working at a fixed condition and showed the effect of WHR system. The system could work at both acceleration and deceleration that is different from the regenerative braking system in a hybrid electrical vehicle (HEV) and provided another option for a HEV to charge the battery that used the regenerative braking system.